2021
DOI: 10.1097/wnp.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

EEG Biomarkers of Repository Corticotropin Injection Treatment

Abstract: Hypsarrhythmia is one of the major diagnostic and treatment response criteria in infantile spasms (IS). The clinical and electrophysiological effect of repository corticotropin injection treatment on IS was evaluated using electrophysiological biomarkers.Methods: Consecutive infants (,24 months) treated with repository corticotropin injection for IS were included in this retrospective descriptive study. Inclusion criteria were (1) clinical IS diagnosis, (2) repository corticotropin injection treatment, and (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…This suggests that a post-treatment decrease in FCN strength is a sensitive but not specific biomarker of favorable treatment response, while an increase in FCN strength is a specific but not sensitive biomarker of treatment non-response. Delta power and coherence showed similar trends, however, the degree of decrease following treatment in both metrics was found to be greater in responders as opposed to non-responders, group wise ( 43 ). Changes in DFA following first-line treatment closely mirrors whether the patient's post-treatment EEG met criteria for hypsarrhythmia or not ( 58 ).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This suggests that a post-treatment decrease in FCN strength is a sensitive but not specific biomarker of favorable treatment response, while an increase in FCN strength is a specific but not sensitive biomarker of treatment non-response. Delta power and coherence showed similar trends, however, the degree of decrease following treatment in both metrics was found to be greater in responders as opposed to non-responders, group wise ( 43 ). Changes in DFA following first-line treatment closely mirrors whether the patient's post-treatment EEG met criteria for hypsarrhythmia or not ( 58 ).…”
Section: Discussionmentioning
confidence: 82%
“…Delta power and delta coherence measured in children with IS before and after ACTH treatment showed that decreases in these measurements following treatment were greater in responders who did not subsequently relapse compared to non-responders and responders who relapsed ( 43 ).…”
Section: Computational Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Only one automated detection study was low risk of bias and found spike rate in a 24-h recording correlated with seizure outcomes following ASM initiation. 78 One moderate-risk-of-bias study 104 detected spikes in only NREM sleep, using both visual detection and Persyst version 13, and found it correlated to seizure outcomes. Two moderate-risk-of-bias studies 53,54 and a high-riskof-bias case report 95 used 1-3 months of RNS system recordings to support IED rate as a biomarker of ASM efficacy.…”
Section: T a B L E 4 Studies That Investigated The Association Of Vis...mentioning
confidence: 99%
“…Eleven studies 44,62,[101][102][103][104][105][106][107][108][109] of both qualitative and quantitative biomarkers investigated short courses of adrenocorticotropic hormone or corticosteroids and compared results to freedom from epileptic spasm during the treatment course and relapse following course completion.…”
Section: Dose Adjustmentmentioning
confidence: 99%